A review of the genus Anelastes Kirby, 1819 (Coleoptera: Eucnemidae) of the Palaearctic fauna - Kovalev, Alexey V. (Zootaxa, 2019)
The genus Anelastes Kirby, 1819 of the Palaearctic fauna is revised. An amended diagnosis of the genus is elaborated. Two new species from North Africa, Anelastes abbreviatus sp. nov. and A. alius sp. nov. are described. Anelastes barbarus P.H. Lucas, 1846 and A. crenulatus (Bonvouloir, 1875) are redescribed and the lectotypes of both species are designated. A key to the Palaearctic species is provided. Anelastes barbarus is newly recorded from Uzbekistan.